Спектри та термодинамічні властивості зигза-гоподібних одностінних вуглецевих нанотрубок з потенціалом Денга–Фана–Хюльтена - Otete, I.; Enaroseha, Omamoke O.E.; Okunzuwa, S.I.; Ejere, A.I.I. (Publishing house "Academperiodika", 2024)
A theoretical investigation of the spectra and thermodynamic properties of zig-zag single-walled carbon nanotubes (6,0) is carried out within the framework of the Deng–Fan–Hulthen potential. We solved the Schr¨odinger wave equation analytically in the presence of magnetic and Aharonov–Bohm (AB) flux fields using the Nikiforov–Uvarov (NU) method and obtained the energy eigenvalues and eigenfunctions. It is observed that, in the absence of both magnetic and AB fields, there is a degeneracy in the energy spectra. The presence of the magnetic and AB flux fields led to an increase in the energy eigenvalues. The combined presence of both fields removed the degeneracy noticed in the system. We calculated the partition function and used it to evaluate the thermodynamic properties such as the mean energy, free energy, and entropy in respect to the temperature, magnetic field, AB flux field and the quantum numbers.